(untitled) (Eurasian Journal of Ecology, 2016)
In this article is researching influence of heavy metals (Mn, Co, Ni) on soils at Ili river downstream. According research data we identified that soil in this region accumulates heavy metals, especially Mn, Co, Ni, what causes entry them in plants via “soil-plant ” system. In research results we identified that cobolt level in soil exceed Maximum Possible Concentration in all 3 points of current location.